Development of elementary teachers' science, technology, engineering, arts, and mathematics planning practices. (8th April 2020) - Cook, Kristin; Bush, Sarah; Cox, Richard; Edelen, Dan
Abstract: The purpose of this instrumental case study was to understand elementary teachers' planning of Science, Technology, Engineering, Arts, and Mathematics (STEAM) curriculum during a two‐year professional development experience. This research was guided by the following question: What planning practices developed or changed during a professional development experience? Analysis of 25 teachers' planning documents indicated growth in the following areas: (a) tighter alignment to fewer standards, (b) more meaningful integration and broader definitions of arts and technology, and (c) increased use of formative assessment but persistent difficulties in summatively assessing the multiple disciplines of STEAM. The growth in teachers' STEAM instruction from the beginning to the end of this two‐year professional development was important in building our understanding of what constitutes sound design of STEAM inquiries.